Media Medan Perkalian dan Pembagian Bilangan Bulat - Salim Salim (Pusat Pengembangan dan Pemberdayaan Pendidik dan Tenaga Kependidikan Matematika, 2020)
Mathematics is considered as a difficult subject for some students, leading to a decrease in students’ interest and motivation in understanding mathematical concept. In the process of classroom teaching and learning, mathematics that seems complicated and makes a bad impression for some students is an obstacle for them in solving daily mathematical problems. To deal with this obstacle, a media innovation in mathematics teaching and learning is deemed necessary as a bridge for students to understand the abstract concepts of mathematical objects through the manipulation of real objects. This paper aims to present how to create and use the media of Medan Perkalian dan Pembagian Bilangan Bulat for elementary school students. This media are quite appropriate as a learning medium used to help students understand the concept of multiplication and division, especially for grade II of elementary school students. Using this medium, students are not only capable to deal with multiplication and the division of integers but also easily understand the concept of multiplication and integers division.